Deposition And Characterization Of Polyfluorene / Cerium Oxide Organic-Inorganic Thin Films - Ahmad, Farah Hayati Haji (2022)
The investigation of a novel approach by applying an organic polyfluorenes (PFs) layer on inorganic high dielectric constant (k) cerium oxide (CeO2) film for potential use as passivation of silicon (Si)-based metal-oxide-semiconductor (MOS) devices was carried out. Initially, the effects of post-deposition annealing temperatures (400, 600, 800, and 1000 °C) was carried out onto the CeO2 films in order to investigate the changes of temperatures onto structural, morphological, optical and electrical characteristics of the CeO2 films. Subsequently, different composition of PFs was dissolved in toluene and deposited onto indium tin oxide glass substrate to examine the effects of varying PFs composition onto the optical, structural, morphological and electrical properties of the PFs. The optimised PFs composition was then applied as an overlayer stacked on CeO2 films post-deposition annealed at different temperatures to fabricate functional Al/PFs/CeO2/Si/Al hybrid organic-inorganic Si-based MOS device, which was relatively new. Structural, morphological, optical, and electrical properties demonstrated by the stacking PFs on CeO2 films were compared with the samples consisting of single CeO2 films. Outcome of the study revealed that the samples having stacking of PFs on CeO2 films could not surpass the performance provided by single CeO2 films. Nonetheless, the stacking of PFs on CeO2 films provided a breakthrough in the context as a potential high k passivation layer to replace the conventional low k silicon oxide (SiO2) due to the adequately higher k value and comparable current-voltage characteristics with CeO2.